1999
DOI: 10.1002/j.2050-0416.1999.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Fusarium Mycotoxins on Growth of Brewing Yeasts. 1 Zearalenone and Fumonisin B1*

Abstract: The Fusarium mycotoxins zearalenone (ZEA) andfumonisin B7 (FBj) added to the growth medium in low and high concentrations, were investigated as a possible cause of inhibition ofgrowth of Saccharomyces cerevisiae lager and ale strains. Toxic effects were assessed by measurement of dry weight or growth relative to controls, cell number, viability and conductance changes of the growth medium using indirect and direct methods. Hie Fusarium mycotoxins studied affected growth on brewing yeasts, but the inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The toxicogenic effects of DON and related mycotoxins are well established for animals and humans (for a review, see reference 165), leading to the adoption of strict quality standards for DON in malt. In addition to potentially threatening human health, high concentrations of these mycotoxins have been shown to inhibit yeast growth during beer fermentation (166,167).…”
Section: Barleymentioning
confidence: 99%
“…The toxicogenic effects of DON and related mycotoxins are well established for animals and humans (for a review, see reference 165), leading to the adoption of strict quality standards for DON in malt. In addition to potentially threatening human health, high concentrations of these mycotoxins have been shown to inhibit yeast growth during beer fermentation (166,167).…”
Section: Barleymentioning
confidence: 99%
“…The variation in the mycotoxin effects in our study may partly be owed to the differences in the structure of the plasma membrane between the species and even between the strains of the same species (18).…”
Section: Place For Tablementioning
confidence: 86%
“…Dziuba et al (5) reported strong inhibition of yeast growth by diacetoxyscirpenol (DAS), a trichothecenes mycotoxin, while ZEA and OTA had a weaker effect. Boeira et al (18)(19)(20) reported significant yeast growth inhibition by the Fusarium toxins, ZEA, DON, and fumonisin B1 (FB1). Similar findings were reported for the trichothecene, T-2 toxin by Foszczyńska and Dziuba (6), and some authors (5,8,17,21,22) have reported that mycotoxins inhibit alcohol dehydrogenase activity and consequently fermentation, lower CO2 release, and affect the production of volatile fermentation by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence the concentration in the final product (raw materials, production steps in the breweries such as the mashing step, fermentation, yeast type). They have been shown to disturb yeast metabolism during fermentation (Boeira, Bryce, Stewart, and Flannigan, 1999a, 1999bKoshinsky, Crosby, & Khachhatourians, 1992;Whitehead & Flannigan, 1989). Several mycotoxins, like trichothecenes, are water soluble and are extracted into wort during mashing.…”
Section: Mycotoxins In Brewing and Beermentioning
confidence: 99%
“…Cantrell (2008) concluded that the majority (65-100%) of T-2 and HT-2 toxins present in malt persist into beer. The degree of growth inhibition has been shown to depend on the toxin concentration, yeast type, fermentation conditions and length (Boeira et al, 1999a(Boeira et al, , 1999bBoeira, Bryce, Stewart, Flannigan, 2002). Furthermore, mashing conditions and enzymatic activity may contribute to the release of mycotoxins from the grain matrix during mashing (Wolf-Hall, 2007).…”
Section: Mycotoxins In Brewing and Beermentioning
confidence: 99%